Phylogenetic analysis among five medicinally significant Phyllanthus L. Species in Bangladesh based on taxonomic and molecular approach - Rahman, Md Shahidur; Hassan , Md Abul; Sultana, Syeda Sharmeen (Dhaka University Journal of Biological Sciences, 2024)
A combination of taxonomical and molecular technique had done for authentic characterization of medicinally important five Phyllanthus species viz. P. acidus, P. emblica (small and large fruit form), P. niruri, P. reticulatus and P. urinaria. They were analyzed with several taxonomical parameters such as branching pattern, morphology of bark, leaves, flowers, fruits and seeds. A dichotomous bracketed key is created for easy identification of the species. RAPD analysis of five Phyllanthus species displayed that P. emblica and P. reticulatus were closely related whereas P. acidus and P. emblica were genetically distantly related. The genus Phyllanthus are diverse, as seen by the 71.68% polymorphism among the five studied species determined by RAPD analysis. The two forms (small and large fruit forms) of P. emblica showed similarity as well as dissimilarity in taxonomic and molecular features. Thus, a subtle revision is necessary in the taxonomical point of view to update their taxa. Dhaka Univ. J. Biol. Sci. 33(1): 121-131, 2024 (January)